The pharmacogenetics antiepileptic drugs - N. A. Shnayder; D. V. Dmitrenko; M. S. Pilugina (Бюллетень сибирской медицины)
There are some generalized data on a problem pharmacogenetics researches antiepileptic drugs on the basis of the analysis of the accessible native and foreign literature in this review.